Experiencing very long term imprisonment from young adulthood: identity, adaptation and penal legitimacy - Crewe, Ben (UK Data Service, 2015)
Interview [format: audio file and Word transcripts] and survey data [format: SPSS and hard-copy], generated with male and female prisoners in England who received long life sentences (minimum 15 years or more) when aged 25 or under. This study will explore the experiences of prisoners who are given very long sentences (15 years or more) when aged under twenty-one. Around one hundred interviews will be conducted with prisoners at various stages of such sentences, as well a smaller number of interviews with prison staff and managers. The main aim is to provide a detailed account of the experiences of these prisoners, focusing on three main areas: - how they cope with (and develop during) such long sentences, and how they manage issues of self and identity. - how they adapt socially to imprisonment, in particular, their relationships with staff and other prisoners, and their levels of compliance, engagement and resistance. - how their sentence conditions and lives prior to imprisonment shape their perceptions of penal legitimacy. The research will contribute to policy and practice in a range of areas, for example, by better informing relevant policymakers and practitioners about the consequences of new sentencing practices, about the needs of this group of very long-term prisoners, and about the operational challenges resulting from the growing number of prisoners serving very long sentences from an early age.